BRIDA: Urgensi Pembentukan dan Posisi Strategisnya Sebagai Solusi Permasalahan Pembangunan dan Peningkatan Kinerja Pemerintahan Daerah - Herie Saksono (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2021)
The establishment of the Regional Research and Innovation Agency (BRIDA) as a localapparatus will bring innovation, especially as an arranger for research and development activities inthe regions. The business processes of the BRIDA must stimulate the creation of new research andinnovation governance in the regions so that the products produced are of more tangible benefit andhave a massive impact on the public benefit. Reform of research and innovation governance isnecessary and should be targeted as the main target and raison d'etre of the establishment of theBRIDA - not only by local governments but also because of government intervention throughconsiderations given by the National Research and Innovation Agency (BRIN). The researchquestions are, who should be the target for the innovation of research and governance in the regions?What should be prepared by the BRIN in response to establishing the BRIDA? This study aims to mapthe existence, role, and management design of the BRIDA. It is hoped that the BRIDA will be able tobecome a regional apparatus that is strong, professional, and adaptive in carrying out the mandate ofresearch, development, assessment, and application, as well as inventions and innovations in theregions. This study uses a qualitative-exploratory approach. The data refers to regulations/policiesgoverning the formation of regional apparatus and elaborating national/regional development planning documents. The conclusion showed that the establishment of the BRIDA should be guided bythe grand design of research and innovation governance in the regions determined by the BRIN.Several mandates are entrusted to the BRIN. In contrast, the BRIDA is expected to be able to play anactive role as a catalyst for improving government performance and accelerating regionaldevelopment. Therefore, it is recommended that the BRIN compile a comprehensive-adaptivemanagement design for the BRIDA by taking into account aspects of managerial novelty, coherencebetween national priority agendas, local government performance targets, and meeting the basicneeds of the community in achieving regional and autonomy goals.